Convivialidade clubística digital: um estudo etnográfico sobre o grupo do Facebook Ceará Sporting Club - Ribeiro, Marcelo da Silva (2017)
The use of social networks on the internet by football fans gives new dynamics and scenarios to the supporting practice. This dissertation results of a qualitative and ethnographic research, fulfilled between mid 2015 to the early 2017, about the daily of an online group’s fans linked to the association of the soccer team called “Ceará Sporting Club”. This group is located on the internet sociotechnical network called “Facebook” and his name is the same as the soccer club that to which its participants are fans, the Ceará Sporting Club (CSC) group. Through a field research made in a interstice of cyberspace and grounded, fundamentally, in the cross of a continuous participate observation and interviews with key interlocutors, this study seek to comprehend by a ethnographic description, how the fans operationalize their ways of supporting to experiencing their fan condition in that digital setting? Tributary of a social anthropology and daily life sociology, this investigation established theorists dialogues with authors as Deleuze and Guattari, Bruno Latour and Michel de Certeau, which provided powerful analytic tools to better understand the empirical field’s dynamic of research. The interactions experienced by the CSC’s participants are inserted in an digital club conviviality gestated in that supporting territory, online space to the supporting practice that is crossed by organizational strategies thought particularly by the group’s moderation and by nomadic tactics which guarantee the interactive dynamism between the members and the published contents in CSC. In both cases, these tactics and strategies are results of an association between technical entities (non-humans actors) from the Facebook’s platform and the CSC’s participants (human actors). In this online space of supporting, the club engagement presents itself something practiced daily by active members of CSC, and one of the means that engagement is more evidenced is by the quest of privileged information about the day-by-day of the football association for whom the participants feed their club passion.